1973
DOI: 10.1172/jci107303
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for Measurement of Thyroglobulin in Human Serum

Abstract: A B S T R A C T A specific and reproducible double antibody radioimmunoassay for the measurement of thyroglobulin (HTg) in human serum has been developed. Since antithyroglobulin autoantibodies combine with the ["3'I] HTg tracer, antibody-positive sera were rejected for measurement. Specificity is demonstrated in that thyroid analogous such as thyroxine (T4), triiodothyronine (T3) monoiodotyrosine (MIT) and diiodotyrosine (DIT) did not crossreact. Sera previously reacted with anti-HTg-Sepharose contained no im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
2
6

Year Published

1979
1979
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(126 citation statements)
references
References 17 publications
3
115
2
6
Order By: Relevance
“…Concerning the sex differences in serum Tg values, some workers (Van Herle et al, 1973 ;Pezzino et al, 1977 ;Pacini et al, 1980) reported significantly higher values in healthy females than in healthy males. Other workers, however, did not find significant difference (Roitt and Torrigiani, 1967 ;Torrigiani et al, 1969 ;Ochi et al, 1975 ;Gardner et al, 1979).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Concerning the sex differences in serum Tg values, some workers (Van Herle et al, 1973 ;Pezzino et al, 1977 ;Pacini et al, 1980) reported significantly higher values in healthy females than in healthy males. Other workers, however, did not find significant difference (Roitt and Torrigiani, 1967 ;Torrigiani et al, 1969 ;Ochi et al, 1975 ;Gardner et al, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies (Van Herle et al, 1973 ;Izumi and Larsen, 1978 ;Gardner et al, 1979;Pacini et al, 1980) have demonstrated varying degrees of elevated levels of serum Tg in thyroid diseases such as Graves' disease and subacute thyroiditis. In patients with thyroid carcinoma, Tg is a useful marker for their follow-up (Van Herle and Uller, 1975 ;Pacini et al, 1980), since the levels of serum Tg after thyroidectomy are low or undetectable in patients with complete remission, whereas elevated serum Tg indicates metastasis and/or recurrence of carcinoma.…”
mentioning
confidence: 97%
“…Several of these early studies (48)(49)(50) reported that Tg was undetectable in some healthy participants. For example, a small study conducted by Hjort et al (48) used a RIA with a limit of detection (LoD) of 50 lg/L and found that Tg was undetected in all 12 healthy subjects, indicating that these subjects would likely have had Tg concentrations £50 lg/L.…”
Section: Methods To Measure Tg Concentrationmentioning
confidence: 99%
“…According to van Herle et al (1) washing the precipitate is not necessary. This discrepancy may be due to the different assay volumes used.…”
Section: Schlumberger and Van Herlementioning
confidence: 99%
“…Scveral methods have been published for the thyroglobuiin assay (1)(2)(3)(4). Radioimmunoassay has found wide application, and most assays employ the double antibody procedure.…”
Section: Introductionmentioning
confidence: 99%